Clinical characteristics of neonatal mortality in a tertiary level hospital in Paraguay: a retrospective observational study. - Cantero Noguera, Cielos Jemima; Colmán Gómez, Deisy Beatriz; Oviedo Ramírez, Shirley Rocío; Cordone Ramos, Alba María (Medicina Clínica y Social, 2023)
Introduction: Neonatal mortality remains a major public health problem worldwide, particularly in developing countries. Most neonatal deaths are attributable to preventable complications, such as premature birth, neonatal sepsis, and birth asphyxia. Objective: To determine the clinical characteristics of neonatal mortality in a tertiary-level hospital in Paraguay through a retrospective observational study. Methods: This observational, descriptive, and retrospective study was conducted at the Hospital de Clínicas in Paraguay. This design allowed information to be obtained from the medical records of newborns who attended the hospital over a period of five years. Results: Between 2018 and 2022, 121 cases of neonatal mortality were recorded at the Hospital de Clínicas del Paraguay. The mean birth weight was 2013.51 ± 1021 kg and mean gestational age was 32.87 ± 4.6 weeks. The most frequent diagnoses of neonatal death were sepsis (37 cases), cardiac involvement (61 cases), and genetic syndromes (39 cases). Discussion: The data obtained from this study suggest that maternal and neonatal risk factors are associated with neonatal mortality in the Hospital de Clínicas of Paraguay. Further studies are needed to analyze these factors and develop preventive strategies to reduce the neonatal mortality rate in the country